Tuberculous Pyonephrosis Involving Duplex Kidney: First Reported Case - Tanweer A.N. Bhatty; Ahmed M. Alkhayat (The Scientific World Journal)
We report a case of tuberculosis (TB) involving duplex kidney that has not been reported in the literature so far. Conservative surgery was done, which was effective in our case.